Quantitation of Cannabinoids in Cannabis Dried Plant Materials, Concentrates, and Oils Using Liquid Chromatography-Diode Array Detection Technique with Optional Mass Spectrometric Detection: Single-Laboratory Validation Study, First Action 2018.11 - Vaclavik, Lukas; Benes, Frantisek; Fenclova, Marie; Hricko, Jiri; Krmela, Ales; Svobodova, Veronika; Hajslova, Jana; Mastovska, Katerina (Journal of AOAC International, 2019)
This paper describes a single-laboratory validation of a liquid chromatography-diode array detection (LC-DAD) method for quantification of 12 major cannabinoids in Cannabis dried plant materials, concentrates, and oils. The method met Standard Method Performance Requirements for quantitative analysis of cannabinoids in Cannabis concentrates and Cannabis dried plant materials. The LOQs were in the range 0.003-0.10% (w/w), depending on the analyte and matrix. Spike recoveries were between 96.7 and 101.3% with relative SDs (RSDs) ≤2.3%. Precision expressed as repeatability and intermediate precision was within 0.3-4.8 and 1.1-5.1%, respectively. The chromatographic separation conditions used in this versatile method are compatible with both DAD-UV and MS detection. During method validation, high-resolution quadrupole time-of-flight MS was employed as a secondary detector (connected in series to the LC-DAD instrument) to provide high confidence identification of target analytes and as a tool for monitoring other cannabinoids for which reference standards were not available. The obtained results demonstrate applicability of the method to quantitative analysis of important cannabinoids in dried plants, concentrates, and oils. Limited data were generated for a food matrix (Cannabis-containing cookies) using this method with LC coupled to a compact single quadrupole mass spectrometer.
Keywords: analýza potravin; kanabinoidy; Cannabis; Plant Extracts; Cannabinoids; Mass Spectrometry; Chromatography, Liquid; rostlinné extrakty; Plant Oils; hmotnostní spektrometrie; chromatografie kapalinová; Food Analysis; oleje rostlin